Socio-economic and Psychological Factors Affecting Clothing Consumption Among Female Undergraduates in University of Uyo, Nigeria - Ngozi U. Nwonye; Myrtle U. Ibokette; Priscilla A. Esiowu (International Journal of Home Economics, Hospitality and Allied Research)
This study explores the socio-economic and psychological factors that shape clothing consumption patterns among female undergraduate students at the University of Uyo, Nigeria. While existing research has extensively examined clothing preferences in various global contexts, limited attention has been given to the unique dynamics between financial constraints and psychological motivations in low-resource settings, particularly within Nigeria. Adopting a descriptive survey design, data were gathered from 389 respondents using a structured questionnaire. The findings highlight the pivotal roles of monthly allowances, the prevalence of second-hand shopping, and psychological influences such as self-esteem and peer pressure in shaping students' clothing choices. This study provides fresh insights by examining the coexistence of socio-economic limitations and identity-driven motivations in a cultural landscape marked by financial challenges and shifting social expectations. The results illuminate how young consumers navigate the interplay between affordability, self-expression, and the need for social acceptance. These findings offer valuable implications for stakeholders, including retailers, policymakers, and educators, by emphasizing the need for interventions that encourage affordable and sustainable fashion, foster financial literacy, and address the psychological effects of clothing consumption.